KAJIAN TEORITIK PERILAKU AKUNTAN BERBASIS STANDAR GOOD CORPORATE GOVERNANCE (GCG) DI PERBANKAN SYARIAH DI KOTA MALANG - Siti Zubaidah (Jurnal Reviu Akuntansi dan Keuangan)
This study aims at long-term to analyze the behavior of accountants based on Good CorporateGovernance (GCG) standard in Sharia Banking. The specific target you want to achieve is to mapthe accountant’s behavior profile. The method used to achieve this goal is by using descriptiveanalysis. This study uses accountant respondents are all independent auditors who work atPublic Accounting Firm (KAP) located in the city of Malang. The sampling technique uses judgment sampling which is one of the purposive sampling. Judgment sampling is to select a samplebased on an assessment of some characteristics of sample members that are tailored to theintent of the researcher. Characteristics of this study sample is the auditor KAP in the city ofMalang who has had experience working as an auditor in Islamic banking at least 1 year. Datawere collected through questionnaire and analyzed by descriptive method which describe andexplain about behavior of accountant in syariah banking. The results of this study indicate theconcept or formulation of the accountant’s behavior in conducting audits and a set of usefulknowledge to enrich the scientific field of Islamic accounting (transparency), accountability,responsibility, professionalism and fairness.Keywords:Accountant behavior, GCG, sharia banking.